2007
DOI: 10.2478/s11756-007-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic activities of ten imidazole derivatives in Salmonella typhimurium

Abstract: Ten imidazole derivatives were tested for mutagenicity in Salmonella typhimurium strains TA98 and TA100 both in the absence and presence of metabolic activation by the microsomal fraction S9 mix. In a general manner, derivatives tested exhibited a greater mutagenic activity in the TA100 strain comparing to the responses in TA 98. In the standard plate incorporation assay, 8 of these substances (80%) were found to be mutagenic for at least one of the two strains in the presence or absence of metabolic activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Literature shows that the position and nature of substituents on phenyl ring greatly effect the mutagenic results [29] as in compound 4d chloro group is present at Meta position of phenyl ring and causes mutagenicity against both strains of Salmonella TA98 and TA 100 while in compound 4e nitro group is also present at meta position but it is mutagenic only for one strain. It shows that chloro and nitro groups at meta position creates greater interaction with DNA and becomes stable [30] and this stability causes genetic mutation in bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that the position and nature of substituents on phenyl ring greatly effect the mutagenic results [29] as in compound 4d chloro group is present at Meta position of phenyl ring and causes mutagenicity against both strains of Salmonella TA98 and TA 100 while in compound 4e nitro group is also present at meta position but it is mutagenic only for one strain. It shows that chloro and nitro groups at meta position creates greater interaction with DNA and becomes stable [30] and this stability causes genetic mutation in bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco wastewater was also shown to be toxic to coliforms (Sponza, 2002). Therefore, this test has a large anticipating value for cancer formation (Aydogan and Kutlu 2007;Benkli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…6 In the past years, a large number of imidazolinone derivatives have been prepared and studied for their antimicrobial activities. [7][8][9][10] Moreover, it has been reported that if imidazol-5(4H)-ones are coupled to the benzylidene moiety, the resulting compounds possess significant antimicrobial activity. 11 In addition, 1,2,4-triazine derivatives have been found to exhibit a variety of biological roles such as antifungal, anti-HIV, anti-malarial, antihypertensive and antibacterial activities.…”
mentioning
confidence: 99%